UNCITRAL Approaches to Regulate Electronic Contracting. Are They Still Applicable? Based on Ukrainian and Other СIS Countries’ Experience - DUDENKO, Tetiana; FILATOVA, Nataliia; KHODYKO, Iurii (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019DO - 10.14505/jarle.v10.8(46).10, 2019)
Contract formation by electronic means nowadays is a widespread phenomenon. Although electronic contracting has been thoroughly analyzed by scholars, there still remain some issues which need to be addressed. In our view, the most essential question raised by electronic contracting is whether there is a need to amend substantial contract law provisions with regard to peculiarities of contracts formed by electronic means. Seeking the answer to this question the UNCITRAL developed several basic approaches which come down to the idea that there is no need to amend substantial contract law provisions and create a special regulation for electronic contracting. However, a lot of countries have deviated from this approach and amended some special rules. In this article the latest amendments of contract law provisions in the CIS countries as well as the provisions on contract formation which remained untouched are critically analyzed. Based on this analysis the following conclusion is made: the principles of functional equivalence and technology neutrality are still applicable to practice of electronic contracting. However, the ‘contract law neutrality’ approach should be carefully rethought since in some cases there is a need to adapt current contract law provisions to the new realm and new practices of contract formation.